2003
DOI: 10.1128/aem.69.11.6489-6494.2003
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin (Oxacillin)-Resistant Staphylococcus aureus Strains Isolated from Major Food Animals and Their Potential Transmission to Humans

Abstract: , various types of specimens from cattle, pigs, and chickens were collected and examined for the presence of methicillin (oxacillin)-resistant Staphylococcus aureus (MRSA). S. aureus was isolated and positively identified by using Gram staining, colony morphology, tests for coagulase and urease activities, and an API Staph Ident system. Among 1,913 specimens collected from the animals, 421 contained S. aureus; of these, 28 contained S. aureus resistant to concentrations of oxacillin higher than 2 g/ml. Isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
370
11
20

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 488 publications
(425 citation statements)
references
References 28 publications
24
370
11
20
Order By: Relevance
“…In the current work, the strains under the study showed high resistance to the mostly widely used antimicrobials and they were resistant to three or more of antimicrobials. Meanwhile, lower percentages were previously recorded in other localities [30]. This high resistance in the studied S. aureus to antimicrobials may be attributed to random use of antibiotics or the public hygienic conditions.…”
Section: Discussioncontrasting
confidence: 51%
“…In the current work, the strains under the study showed high resistance to the mostly widely used antimicrobials and they were resistant to three or more of antimicrobials. Meanwhile, lower percentages were previously recorded in other localities [30]. This high resistance in the studied S. aureus to antimicrobials may be attributed to random use of antibiotics or the public hygienic conditions.…”
Section: Discussioncontrasting
confidence: 51%
“…Atanassova et al found 51.1% S. aureus contamination in raw pork meat by PCR detection while he claimed 57.7% S. aureus contamination by using classical microbiological procedures [27] . Heo et al reported 11% S. aureus prevalence in meat, while Lee reported 13% S. aureus presence in poultry meat of Korea [15,28] .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, methicillin-resistant S. aureus (MRSA), which are resistant to almost all types of β-lactam antimicrobials, have been a concern worldwide (Lee 2003, Van Duijkeren et al 2004. The presence of MRSA in dairy cows has been investigated because it was demonstrated that cattle may serve as a source of emergence of new MRSA strains in humans (Juhász-Kaszanyitzky et al 2007, Vanderhaeghen et al 2010.…”
Section: Introductionmentioning
confidence: 99%